Calcifications valvulaires chez l'hémodialysé au Maroc - Faqih, Samia Ait (Pan Afr Med J, 2016)
INTRODUCTION: Valvular calcifications are one of the major cardiovascular complications of hemodialysis because of its prevalence and its predictive indices of morbidity and mortality. There are many risk factors associated with these calcifications. Our study aims to evaluate both the prevalence of valvular calcifications in our patients on hemodialysis and their risk factors. METHODS: This was a single-center cross-sectional descriptive and analytical study of 111 adult patients who were on hemodialysis for more than 6 months at the hemodialysis center CHU Ibn Rushd, Casablanca and who underwent ETT during the year 2013. RESULTS: The average age of our patients was 44 ± 14 years. The average duration of hemodialysis was 146 ± 80 months. Average systolic blood pressure was 123 ± 23 mmHg and average diastolic blood pressure 72 ± 13 mmHg diastolic, average iPTH was 529 ± 460 pg/ml, mean serum calcium was 86 ± 10 mg/l and mean serum phosphate was 40 ± 15 mg/l. Mean CRP level was 11±19,8 mg/L. From the therapeutic point of view, 96% of patients were treated with calcium carbonate, 11% with 25 OH vitamin D, 55,5% with 1 hydroxy-vitamin D3. The prevalence of valvular calcification was 15% with aortic valve location in 41.2% and mitral valve location in 41.2%. In univariate analysis, only hemodialysis duration seems to be associated with the occurrence of calcifications and approaches marginal level of significance (p = 0.09). CONCLUSION: The prevalence of valvular calcification in our hemodialysis patients remains high even if it seems relatively low compared to the literature data. No known risk factor was significantly associated with these calcifications.